Credibility of fuzziness: theory and application - Provotar, O.I.; Provotar, O.O. (Інститут програмних систем НАН України, 2018)
An approach to finding a credible estimates of fuzzy events in fuzzy inference systems is considered. Such systems are used to represent fuzzy knowledge, in particular, in expert systems, pattern recognition systems, forecasting systems, and so on. The extraction of knowledge in such systems is carried out with the help of cumbersome intellectual calculations, and the knowledge obtained requires an assessment oftheir сredibility. An example of application of the proposed approach in expert diagnostic system with fuzzy model of presentation of knowledge is given.Problems in programming 2018; 2-3: 164-170